2021
DOI: 10.3389/fgene.2020.607722
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Prognostic Competing Triplets in High-Grade Serous Ovarian Cancer

Abstract: Increasing lncRNA-associated competing triplets were found to play important roles in cancers. With the accumulation of high-throughput sequencing data in public databases, the size of available tumor samples is becoming larger and larger, which introduces new challenges to identify competing triplets. Here, we developed a novel method, called LncMiM, to detect the lncRNA–miRNA–mRNA competing triplets in ovarian cancer with tumor samples from the TCGA database. In LncMiM, non-linear correlation analysis is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Ovarian cancer is famous for its high fatality rate (14). Exploring the molecular mechanism of OC is conducive to finding effective therapeutic targets (15,16). Increasing evidence has suggested that CDK4/6 play important roles in the progression and prognosis of multiple cancers, including OC (17).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is famous for its high fatality rate (14). Exploring the molecular mechanism of OC is conducive to finding effective therapeutic targets (15,16). Increasing evidence has suggested that CDK4/6 play important roles in the progression and prognosis of multiple cancers, including OC (17).…”
Section: Discussionmentioning
confidence: 99%
“… 31 In the miRNA–lncRNA pair centered regulatory network consisting of competing triplets in ovarian cancer, AC099850.4 is one of the top five lncRNAs with the most connections. 32 Studies have shown that LINC02154 is significantly upregulated in renal cell carcinoma, and its high expression is one of the risk factors for poor prognosis. It is involved in the construction of a model for predicting the prognosis of patients with renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, overexpression of MIR210HG promotes the progression of colorectal adenocarcinoma via modulating hypoxia (He et al, 2019) and was associated with worse overall survival in colon cancer patients (Ruan et al, 2019). AC099850.4 is one of the top lncRNA in miRNA-lncRNA network and may be associated with tumor division, tumor proliferation, cell cycle and so on in ovarian cancer (Zhao et al, 2020). Higher expression of NRAV was associated with advanced clinical stage, poor prognosis and immunologic characteristics in hepatocellular carcinoma patients (Feng et al, 2021;Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%